RELIABILITY OF ELECTROMAGNETIC CONVERTER - Sorimsokov Uchqun Soatboy o’g’li, Boliyev Alisher Mardiyevich, Suyarov Anvar Olim o’g’li; Nurullayev O.U. (Zeta Repository, 2023)
Classic single-phase current transformers, Methods for calculating the reliability of elements, Probability of no-failure operation of an electromagnetic converter